PENGARUH PENERAPAN BAGASI BERBAYAR DI MASKAPAI WING AIR TERHADAP MINAT PENUMPANG DI BANDAR UDARA H. HASAN AROEBOESMAN NUSA TENGGARA TIMUR - Rahmat Hidayat; Elnia Frisnawati (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Wings Air is one of the airlines operating in Indonesia. Wings Air (PT Wings Abadi) is a domestic airline based in Jakarta, Indonesia. Wings Air has won the trust of air transportation users with its Low cost Carrier and can accompany transportation users to routes that are not covered by other airlines. The purpose of this study was to determine the effect of the application of paid baggage at Wings Air on the interest of passengers at H.Hasan Aroeboesman Ende Airport. This study uses quantitative research methods. Data collection techniques used questionnaires and literature studies. The instrument used as a data collection tool was in the form of a questionnaire, for indirect interview and observation guidelines. Data analysis using Validity Test, Reliability Test, Hypothesis Testing, Simple Linear Regression, Coefficient of Determination. The results of this study indicate that Ha is accepted and Ho is rejected, which means that there is an effect of the application of paid baggage by Wings Air on the interest of H.Hasan Aroesboeman Ende Airport passengers, as evidenced by hypothesis testing, it is known that the value of t count > t table, namely 12.999> 1.98422 with sig. 0.000 < 0.05 . The percentage based on the coefficient of determination test is known that R square is 0.633, this means that the influence of the application of paid baggage for Wings Air on the interest of passengers at H.Hasan Aroesboeman Ende Airport is 63.3%.